Pelatihan Penyusunan Projek Penguatan Profil Pelajar Pancasila di SDN 36 Cakranegara - Nurwahidah; Novitasari, Setiani; Angga, Prayogi Dwina; Wardani, Ketut Sri Kusuma; Nurmawanti, Iva (Universitas Mataram, 2024)
The aim of the Merdeka Curriculum is to strengthen the achievement of the Pancasila Student Profile. The Pancasila Student Profile was developed to create democratic, superior, and productive Indonesian citizens in the 21st century. So that students are expected to be able to participate in sustainable global development and be resilient in facing various challenges during the Industrial Revolution 4.0. Teachers as educators and facilitators are expected to be able to implement the Project for Strengthening the Pancasila Student Profile in the Independent Curriculum for students. The implementation of this new curriculum makes it difficult for teachers at SDN 36 Cakranegara, especially in implementing it in the learning process. One of the difficulties is that teachers lack information regarding the preparation of projects to optimally strengthen the profile of Pancasila students. So training is needed to prepare projects to strengthen the profile of Pancasila students. The implementation of the training went well, and the teachers were very enthusiastic about participating in the activities. Several questions were asked by the teacher, including regarding the differences between the project to strengthen the Pancasila student profile and the project learning model, how to determine the project and realize it. The results of the training showed that teachers obtained information and understood the preparation of the project to strengthen the profile of Pancasila students to support the implementation of the Independent Curriculum in schools.